Plasma concentrations of lignocaine during fibreoptic bronchoscopy. - Efthimiou, J (1982)
Peak plasma concentrations of lignocaine were recorded in 41 patients receiving topically applied lignocaine for fiberoptic bronchoscopy. Adequate anaesthesia was achieved in all patients with an average dose per unit weight of 9.3 +/- 0.5 mg/kg (SEM) giving a mean peak plasma concentration of 2.9 +/- 0.5 mg/l-1 (SEM) (+/- SEM 0.5). The plasma concentration exceeded toxic levels of 5.0 mg/l-1 in only two patients, and no complications were observed. Peak concentrations were influenced only by dose per unit weight administered and not by factors considered likely to influence mucosal absorption from the bronchial tree, such as sputum production, airflow obstruction, or cigarette smoking. A major proportion of the total dose of lignocaine was required to anaesthetise the nose, pharynx, and larynx, only a small proportion being needed for the bronchial tree. Lignocaine gel (2% w/v) was preferred by patients, and in a study of 10 volunteers, produced lower plasma concentrations when used as a topical anaesthetic than did lignocaine aerosol (10% w/v) or lignocaine solution (4% w/v).